Synthesis of Bungeanool, Isobungeanool, Dihydrobungeanool, Tetrahydrobungeanool, Hazaleamide, Lanyuamide III, and Analogues - Loo, Ying-Hui; Leakasindhu, Suleeporn; Kan, Chi-Ming; Toy, Patrick H. (Synthesis, 2021)
The bungeanools are a family of alkamide natural products isolated from the pericarps of Zanthoxylum bungeanum (Sichuan pepper), and they are structurally related to the sanshools. While the sanshools, especially hydroxy-α-sanshool, have been studied in a variety of contexts, research regarding the bungeanools has been much more limited. To facilitate their study, we have developed stereoselective syntheses of all four members of this family of compounds by using flexible routes that are also amenable to the synthesis of analogues. The key transformation in the syntheses was the stereoselective triphenylphosphine/phenol-catalyzed isomerization of an alkynoate to the corresponding conjugated E,E-dienoate.
Keywords: alkamides; bungeanool; isobungeanool; dihydrobungeanol; tetrahydrobungeanol; hazaleamide; lanyuamide III; natural product synthesis